Steve Keen's The New Economics: A Manifesto - Shimshon Bichler; Jonathan Nitzan (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2021)
Neoclassical economics is the official scientific underpinning of capitalism as well as its main ideological defence, and according to Keen, it fails in both tasks. Contrary to received opinion, neoclassicism cannot explain capitalism – either in detail or in the aggregate – and the policies it prescribes do not support but undermine the very system it defends. It must be scrapped, says Keen, and the purpose of his book is to explain why and outline what should come in its stead.
Keywords: P16; E4; G21; E61; G01; G; E13; Q54; 330; banks; climate; complex systems; credit; debt; finance; macroeconomics; money; neoclassical economics; policy